2011
DOI: 10.4028/www.scientific.net/amr.187.434
|View full text |Cite
|
Sign up to set email alerts
|

Application of Near Infrared Spectroscopy in Wood Water Content Prediction

Abstract: Water content of Korean pine samples was studied using near infrared spectrascopy (NIR) combinded with parial least squares regression (PLS) analysis. Seven typical wave lengths were selceted to characterize the wood water content of Korean pine. Prediction models of wood water content were developed based on the original NIR spectra at seven varied wave lengths. The best model was showed between wavelengths from 1000 to 2100 nm with correlation coefficient (R) of 0.9871, standard error of calibration (SEC) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Seven wavenumbers were selected and partial least squares (PLS) regression was used. The best result was obtained between the 1000 to 2100 cm -1 wavenumber, where the model showed validation correlation coefficient of 0.98 and RMSEP = 0.0465 % (ZHANG et al 2011). The study by Santos et al, (2017) demonstrated that NIR spectroscopy is an efficient technique to estimate wood moisture and monitor water desorption of Eucalyptus urophylla x Eucalyptus grandis.…”
Section: Humiditymentioning
confidence: 90%
“…Seven wavenumbers were selected and partial least squares (PLS) regression was used. The best result was obtained between the 1000 to 2100 cm -1 wavenumber, where the model showed validation correlation coefficient of 0.98 and RMSEP = 0.0465 % (ZHANG et al 2011). The study by Santos et al, (2017) demonstrated that NIR spectroscopy is an efficient technique to estimate wood moisture and monitor water desorption of Eucalyptus urophylla x Eucalyptus grandis.…”
Section: Humiditymentioning
confidence: 90%
“…8. According to Zhang et al (2011), these two peaks can be related to the combination of O-H stretching and O-H deformation of water:…”
Section: Ftir-nir Characterizationmentioning
confidence: 99%
“…Wood water content has little effect on properties (except quality) above the fiber saturation point. On the contrary, a mass of features of wood are influenced evidently by water content below the fiber saturation point, which include wood strength, stiffness, hardness, thermal conductivity, combustion value and so on [1][2][3].…”
Section: Introductionmentioning
confidence: 99%